2014
DOI: 10.1007/s11024-014-9259-9
|View full text |Cite
|
Sign up to set email alerts
|

Research Productivity of Returnees from Study Abroad in Korea, Hong Kong, and Malaysia

Abstract: This study analyzes whether academics with advanced degrees from foreign universities are more research productive than their domestic counterparts in the three selected East Asian higher education systems -Korea, Hong Kong, and Malaysia. The three systems have relatively large proportions of foreign degree holders among their professoriates. The data for this study is drawn from the Changing Academic Profession survey. In our negative binominal regression analysis, we found that foreign degree holders are not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 50 publications
1
54
0
Order By: Relevance
“…Secondly, mobility experiences are increasingly discussed with regards to their effects on academics' scholarly output—more concretely, their research productivity—but the findings are mixed thus far (Bolli & Schlapfer, ; Shin, Jung, Postiglione, & Azman, ). The reason for these mixed findings is twofold.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, mobility experiences are increasingly discussed with regards to their effects on academics' scholarly output—more concretely, their research productivity—but the findings are mixed thus far (Bolli & Schlapfer, ; Shin, Jung, Postiglione, & Azman, ). The reason for these mixed findings is twofold.…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of indicators to measure research productivity -number of publications, citation counts, doctoral students and competitive research funding (Litwin 2012), although there are differences between academic disciplines in terms of the importance attributed to these indicators (Becher and Trowler 2001). Nevertheless, the number of publications, particularly peer-reviewed journal articles, is the most widely used indicator of research productivity across academic disciplines (Toutkoushian and Bellas 2003;Horta, Dautel, and Veloso 2012;Shin et al 2014) since it is the most important stimulant of career progression and also allows for comparative analysis (Litwin 2012).…”
Section: Introductionmentioning
confidence: 99%
“…They have a promising future if these universities aggressively invest resources and upgrade A u s t r a l i a A u s t r i a B e l g i u m B r a z i l C a n a d a C h i n a F i n l a n d F r a n c e G e r m a n y H K I t l a y J a p a n K o r e a M a l a y s i a M e x i c o N e t h e r l a n d s N e w Z e a l a n d s P o r g u g a l R u s s i a S o u t h A f r i c a S p a i n S w e d e n S w i z e r l a n d their systems. As some studies (e.g., Shin et al 2014) have found, the research performance of the domestically trained doctoral degree holders in the region is not lacking in productivity compared with the doctoral degree holders from abroad. The rapid growth of doctoral training in the region has been helped by those graduates who returned from doctoral study at foreign universities as well as the increasing number of internationally mobile academics.…”
Section: Discussionmentioning
confidence: 95%